2021
DOI: 10.3390/ijms22063225
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Guided Mutagenesis of Grain Size 3 Confers Increased Rice (Oryza sativa L.) Grain Length by Regulating Cysteine Proteinase Inhibitor and Ubiquitin-Related Proteins

Abstract: Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein (Cas9)-mediated genome editing has become an important way for molecular breeding in crop plants. To promote rice breeding, we edited the Grain Size 3 (GS3) gene for obtaining valuable and stable long-grain rice mutants. Furthermore, isobaric tags for the relative and absolute quantitation (iTRAQ)-based proteomic method were applied to determine the proteome-wide changes in the GS3 mutants compared with wild type (WT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…This dominant protein plays a crucial role in the transportation of storage proteins and is also involved in the hydrolysis of gluten protein responsible for the rheological properties of dough in wheat (Koehler and Ho, 1990;Capocchi et al, 2000;Mikola et al, 2001;Mäkinen and Arendt, 2012). As reported by (Usman et al, 2021), a mutation in the gene encoding Cysteine proteinase inhibitor protein in rice resulted in a positive regulation during grain development and increased grain yield (Usman et al, 2021).…”
Section: In Silico Analysis Of Candidate Genesmentioning
confidence: 98%
“…This dominant protein plays a crucial role in the transportation of storage proteins and is also involved in the hydrolysis of gluten protein responsible for the rheological properties of dough in wheat (Koehler and Ho, 1990;Capocchi et al, 2000;Mikola et al, 2001;Mäkinen and Arendt, 2012). As reported by (Usman et al, 2021), a mutation in the gene encoding Cysteine proteinase inhibitor protein in rice resulted in a positive regulation during grain development and increased grain yield (Usman et al, 2021).…”
Section: In Silico Analysis Of Candidate Genesmentioning
confidence: 98%
“…The CRISPR/Cas9 technology was then used to create homozygous Gs3 mutation lines with stable inheritance and a long-grain phenotype. Their study offers a simple and effective method for increasing grain production, which may considerably speed up the breeding strategy of long-grain japonica parents and encourage the creation of high-yielding rice [46].…”
Section: Grain Yield Increasementioning
confidence: 99%
“…Other research studies used CRISPR/Cas9 in a similar manner with the aim of producing an observable effect either through gene overexpression or gene knockout in rice. Through these methods, various genes have been identified and successfully manipulated, for example, genes responsible for traits such as pigment (anthocyanin) content (Zheng et al, 2019 ; Hu et al, 2020 ), resistance to disease (bacterial blight and blast disease) (Zhou et al, 2015 ; Wang et al, 2016 ; Kim et al, 2019 ), and grain length (Li et al, 2020a; Usman et al, 2021 ). These findings prove that CRISPR/Cas9 technology is undoubtedly effective in manipulating traits in rice, and it is expected that these methods can be applied to generate more resilient, robust, and nutritious rice, which can drive global sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its popularity, there is still a degree of uncertainty when utilizing this method as its success depends on the choice of the plasmid and the cultivar used (Mangena et al, 2017 ). Various studies have reported that the A. rhizogenes -mediated transformation system could have been the cause of low transformation efficiency observed in soybean (Li et al, 2019 ; Bai et al, 2020 ; Zhang et al, 2020a ), rice (Butt et al, 2017 ; Usman et al, 2021 ), and tomato (Ron et al, 2014 ) genome editing. Varying culture conditions can also influence the infection and regeneration rates of the Agrobacterium- infected explants, which affects the reproducibility of the results obtained (Hamada et al, 2018 ) as observed in soybean (Li et al, 2017; Hada, 2018 ; Mangena, 2018 ), clover ( Trifolium subterraneum L.) (Rojo, 2021 ), and cassava (Nyaboga et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%